"Association between posterior unilateral functional crossbite and asymmetrical spinal flexion: A prospective study". Issue 3 (March 2023) - Piancino, Maria Grazia; Matacena, Giada; Garagiola, Umberto; Naini, Farhad B.; Tortarolo, Alessandro; Wertheim, David
Abstract: Background: Unilateral posterior crossbite (UPC) with functional shift is a malocclusion that may have the potential to affect the masticatory function and the flexibility of the spine due to intrinsic occlusal, structural and functional asymmetries sustained by marked asymmetrical muscular activation. Research question: To investigate whether the presence of UPC with functional shift is associated with reverse chewing pattern and altered spine flexion. Methods: Patients with UPC and a control group of patients with normal occlusion were recorded when chewing soft and hard boluses using a Kinesiograph (Myotronics-Noromed Inc., USA) and spine alignment was assessed with an electronic inclinometer Spinal Mouse® system (Idiag AG, Switzerland). Results: There were 87 children with UPC in the patients' group among whom 38, with median (IQR) age 8.0 (7.3–9.3) years, had measurements before and after treatment. The UPC patients showed a higher percentage of anomalous/reverse chewing patterns on the crossbite side compared with a control group (p < 0.001). Moreover, a clear difference was observed between left and right flexion angles of the spine in the patients' group (p < 0.001 and p = 0.001, paired t -test) with the crossbite side being more flexible compared to the non-crossbite side. No such differences were seen in the control group, nor post-treatment for right and left crossbite (p = 0.44 and p = 0.15 respectively, paired t -test). Significance: This study suggests an association between UPC, asymmetrical chewing patterns and asymmetrical flexion of the spine. These results may help improve understanding of any association between dental malocclusions and spine posture and hence aid diagnosis and treatment strategies. Highlights: Unilateral posterior crossbite is associated with asymmetric flexion of the spine. The degree of flexion was significantly increased on the side of the malocclusion. There was no asymmetry in spine flexion after the correction of the malocclusion. Unilateral posterior crossbite malocclusion is associated with chewing dysfunction. The percentage of reverse chewing cycles was increased on the malocclusion side.